The Brazilian penitentiary system and the inefficiency of the rehabilitation of convicts (Research, Society and Development, 2022)
The article aims to analyze the application of the legal means that lead to the execution of the sentence in the penitentiary system, demonstrating the lack of effectiveness of the Brazilian penitentiary system in terms of resocialization. As methodological aspects, a bibliographic research was adopted, which was based on: articles, monographs, dissertations and theses on the subject, bearing in mind the need to identify the studies already carried out. The results showed that the current situation in which the prison system, in total disagreement with the principles of the Federal Constitution of 1988 and the Criminal Execution Law, where it is necessary to look for ways that allow the real application, and not just in the dead letter of the law, of principles, bringing benefits enjoyed by the whole society. In order for the sector to change, it is necessary to have political movement, which is not very encouraging, as prisoners distance themselves from the priorities of politicians, largely as a result of society's disinterest, who care little about conditions of serving the sentence of a person who commits a crime. However, it is not because of the failure of the system that the abolition of the penalty should be considered. Measures are needed in order to try to reduce the ailments and stigmatization of prisoners, such as privatization, restorative justice and re-socialization through education.